The determinants of mobile-phone usage among small-scale poultry farmers in Ghana. (September 2019) - Folitse, Benjamin Yao; Manteaw, Seth Awuku; Dzandu, Lucy Payne; Obeng-Koranteng, Grace; Bekoe, Stephen
This paper makes the firm assumption that the effective use of ICT tools such as the mobile phone may hold the key to introducing the needed dynamism and efficiency in agricultural extension delivery in Ghana. It therefore seeks to examine the dynamics of the use of mobile phone among poultry farmers in the Greater Accra Region of Ghana. One hundred and fifty poultry farmers selected from the Greater Accra Region were interviewed using structured questionnaires. The study showed a high penetration of mobile phones among the poultry farmers. A regression analysis showed that demographic variables such as age, sex, educational level, experience and size of holdings influenced the use of mobile phone. Network failure was cited as the major constraint to the use of mobile phones. There is the need for the required investment to build a more robust infrastructural base for the use of mobile phone as it remains a critical tool to supporting agricultural extension delivery among Ghanaian farmers.